INEXTENSIBLE FLOWS OF CURVES IN THE EQUIFORM GEOMETRY OF THE PSEUDO-GALILEAN SPACE G31 - Oztekin, Handan; Bozok, Hulya Gun (Turkic World Mathematical Soc, 2016)
In this paper, we study inextensible flows of curves in 3-dimensional pseudo-Galilean space. We give necessary and sufficient conditions for inextensible flows of curves according to equiform geometry in pseudo-Galilean space.
Keywords: inextensible flows; equiform differential geometry; Galilean space; pseudo-Galilean space